THE ROLE OF PLANNING BUDGETS IN FINANCIAL PERFORMANCE (World Bulletin of Social Sciences, 2023)
We suffer at the present time from a lack of commitment to apply planning budgets in an accurate manner, which weakens the control over water resources and the failure to identify deviations, which in turn is likely to affect the financial efficiency . The aim of the research is to know the effect of the budget in planning and control, study the impact of the participation of organizational levels in preparing planning budgets on the efficiency of financial performance, study the effectiveness of planning budgets in controlling cash flow , The various organizational participation in the preparation of the planning budget affects the efficiency of financial performance. It affects the application of cash flow. There is a statistically significant relationship between the proper application of the planning budget and the efficiency of financial performance. The research reached several results, the proper application of planning budgets leads to Raising the efficiency of financial performance Implementation of planning budgets in a good way that makes cash flows regular according to the set plan , which ensures their implementation and thus increases the efficiency of financial performance . It sets clear policies and procedures by the administration for the proper application of the planning budgets system and ensuring its implementation and with the participation of employees in preparing plans, the most important of which is the application of planning budgets in a good way that leads to controlling the cash flow. The researchers recommend the following the need to apply planning budgets in a good manner to control cash flow, the need to apply planning budgets to make cash flows regular according to the plan subject , the need to develop clear policies and procedures by the administration for the proper application of the planning budgets system to ensure its implementation , the need for employees to participate in preparing plans and budgets to ensure their implementation to increase the efficiency of financial performance